Synthetic lethality between HER2 and transaldolase in intrinsically resistant HER2-positive breast cancers. Issue 1 (December 2018) - Ding, Yi; Gong, Chang; Huang, De; Chen, Rui; Sui, Pinpin; Lin, Kevin; Liang, Gehao; Yuan, Lifeng; Xiang, Handan; Chen, Junying; Yin, Tao; Alexander, Peter; et al.
Abstract Intrinsic resistance to anti-HER2 therapy in breast cancer remains an obstacle in the clinic, limiting its efficacy. However, the biological basis for intrinsic resistance is poorly understood. Here we performed a CRISPR/Cas9-mediated loss-of-function genetic profiling and identifiedTALDO1, which encodes the rate-limiting transaldolase (TA) enzyme in the non-oxidative pentose phosphate pathway, as essential for cellular survival following pharmacological HER2 blockade. Suppression of TA increases cell susceptibility to HER2 inhibition in two intrinsically resistant breast cancer cell lines with HER2 amplification. Mechanistically, TA depletion combined with HER2 inhibition significantly reduces cellular NADPH levels, resulting in excessive ROS production and deficient lipid and nucleotide synthesis. Importantly, higher TA expression correlates with poor response to HER2 inhibition in a breast cancer patient cohort. Together, these results pinpoint TA as a novel metabolic enzyme possessing synthetic lethality with HER2 inhibition that can potentially be exploited as a biomarker or target for combination therapy. Resistance to anti-HER2 therapy in breast cancer remains a major obstacle in the clinic. Here the authors performed a CRISPR-selective vulnerability screen to identify transaldoloase as a target that is synthetically lethal with HER2 inhibition in breast cancer cells.